Do Customers Will Accept Seaweed Packaging Innovation?. (July 2020) - Alfaridi, Nursery; Puspitorini, A G; Wicaksono, D J; Octaviani, R D
Abstract: World nowdays is suffering from a lot of environmental issues and one of the causes is plastic waste. Plastic causes hazardous negative impact on environment due to its non-biodegradable nature. The use of plastic majority is for the purpose of packaging. Whereas, there is packaging innovation using seaweed based which is more environmental friendly but the companies that use it are almost nonexistent. This research investigated the customers acceptance if their basic packaging material change from plastic to seaweed and focused on edible food packaging. Methodology used for this research is quantitative method with simple linear regression and SPSS for the data analysis. The purpose of this research is to encourage the company to start changing their packaging material if the customers itself also willing to accept it, and along with to inform customer about the packaging innovation and cooperate to reduce the use of plastic. The result of this research is customers do will accept the seaweed packaging innovation.